(untitled) (International relations and international law Journal, 2016)
Institute of criminal law appeared earlier in Western countries than in Kyrgyzstan. Comparative-legal analysis is very important in taking into consideration the practice of those countries in struggling against production and distribution of counterfeit money and securities. Criminal laws of several European countries were compared with Kyrgyzstan’s Criminal Code, describing differences and advantages within this analytical work. The source of French criminal law is Criminal Code that was accepted by National Congress and Senate in 1992, which consisted of 4 separate laws. Advantages of French legal base were seen during comparison of two countries. As for Germany, Constitution of 1949, Criminal Code of 1871 which was altered in 1988, federal criminal laws and international criminal legislation are the sources of country’s criminal law system. One of the differences of German and Kyrgyz laws is that German laws include more items that refer to this crime. Dutch criminal laws don’t identify as a crime the production of foreign counterfeit money and securities, whereas Bulgaria laws give not the list of items that refer to this crime, but only their characteristics. As a result, analysis of international law brings together a group of foreign states that distinguishes their criminal and legal framework from the legislation of Kyrgyzstan.